2006
DOI: 10.1167/iovs.05-1172
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation byStaphylococcus epidermidison Intraocular Lens Material

Abstract: S. epidermidis formed biofilm most intensely on acrylic among the four IOL materials tested. MPC surface-modified acrylic has a preventive effect on biofilm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 29 publications
4
72
0
Order By: Relevance
“…Our SEM results showed multilayered biofilm formation on the lense surfaces ( Figure 2). Similar observations were noted by Okajima et al [10] who demonstrated that S epidermidis formed biofilms intensely on acrylic lenses and such biofilm formation could be recognized as early as 24 hours postincubation. Our study reflected exactly similar findings.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our SEM results showed multilayered biofilm formation on the lense surfaces ( Figure 2). Similar observations were noted by Okajima et al [10] who demonstrated that S epidermidis formed biofilms intensely on acrylic lenses and such biofilm formation could be recognized as early as 24 hours postincubation. Our study reflected exactly similar findings.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike others [10,18], who noted biofilms on IOLs of various compositions, such as PMMA, silicone or MPC (methacryloyloxyethyl phospharyl choline); we conducted the study using PMMA lenses alone. While Kodjikian et al [18] emphasized only on the SEM study of S epidermidis biofilm on silicone IOL with PMMA haptic, ours was on a different perspective altogether, because we had opted not only to detect biofilm formation, but also to enumerate the bacterial population attaching on PMMA lenses using organisms with different phenotypic and molecular characteristics ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 These microorganisms adhere onto the IOL after implantation, proliferate and colonize subsequently, and then form biofilms on the implanted IOL postoperatively. 3 This bioadhesion greatly influences the clinical effects after the IOL implantation.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38] In addition, surface modification of implantable biomedical devices is an effective way to improve their biocompatibility. [3][4][5][6]39 Cell-resistant surface can be generated via hydrophilic macromolecule immobilization or hydrogel-like surface coating. [40][41][42][43][44][45] In this study, we fabricated the zwitterionic PMPC brush onto the hydrophobic IOL surface via SI-RAFT polymerization.…”
mentioning
confidence: 99%